2011
DOI: 10.1016/j.bone.2011.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression and subcellular protein distribution in MLO-Y4 osteocytic cells by lysophosphatidic acid: Relevance to dendrite outgrowth

Abstract: Osteoblastic and osteocytic cells are highly responsive to the lipid growth factor lysophosphatidic acid (LPA) but the mechanisms by which LPA alters bone cell functions are largely unknown. A major effect of LPA on osteocytic cells is the stimulation of dendrite membrane outgrowth, a process that we predicted to require changes in gene expression and protein distribution. We employed DNA microarrays for global transcriptional profiling of MLO-Y4 osteocytic cells grown for 6 and 24 hours in the presence or abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…In addition, this study demonstrated the dependence on G i to differentiate mature osteoblasts under LPA. Such an effect of LPA on mature osteoblasts is in agreement with its described role in promoting dendrite outgrowth of the osteocyte-like cell line, MLO-Y4 [15,16]. LPA induces changes in the cytoskeleton and stimulates the migration of MC3T3-E1 osteoblastic cells [17].…”
Section: Introductionsupporting
confidence: 74%
“…In addition, this study demonstrated the dependence on G i to differentiate mature osteoblasts under LPA. Such an effect of LPA on mature osteoblasts is in agreement with its described role in promoting dendrite outgrowth of the osteocyte-like cell line, MLO-Y4 [15,16]. LPA induces changes in the cytoskeleton and stimulates the migration of MC3T3-E1 osteoblastic cells [17].…”
Section: Introductionsupporting
confidence: 74%
“…LPA modulates motility in osteoblasts and osteocytes, inducing chemotaxis in murine MC3T3 preosteoblasts 85 and dendrite outgrowth in MLO-Y4 osteoblasts. 86 These findings suggest that LPA may be involved in directing osteoblast migration and morphology during bone remodeling. Recent data provide evidence that osteoclasts produce LPA, which can then act as an additional autocrine signal as well as a paracrine cue to osteoclasts and potentially MSCs.…”
Section: Skeletal Biologymentioning
confidence: 85%
“…Similarly, 423 gene products were regulated at p<0.1 (Supplementary Table 2). As we have done previously (Waters et al, 2011), we then utilized a fold change cut-off to discern gene products of greatest interest. Table 1 identifies all transcripts significantly fluid flow-regulated by at least ±1.5-fold change at any time point, including 13 at p<0.05 and 22 at p<0.1.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of total RNA was carried out as in Waters, et al (Waters et al, 2011). First, quality was verified using an Agilent 2100 Bioanalyzer (Agilent Technologies, Palo Alto, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation